Classroom management problems faced by education administrators in distance education during the pandemic period - Ece, Özlem; Bastas, Mert (Frontiers in Psychology, 2022)
Distance education contributes to the development of teamwork skills that may be needed in business life and builds effective collaborative communication skills that allow individuals to learn on their own. Students are able to take online classes, interact with their teachers and become a member of interactive groups. During the pandemic, countries faced different constraints that changed the general perception of education. The use of distance education programs, especially during the recent global COVID-19 epidemic, has had a positive or negative impact on students and had similar impacts on teachers as well. The education sector has also been affected by the various measures taken by countries to minimize the risk of transmission during the pandemic period. In this period, the traditional understanding of education has been interrupted and teachers carried out their education and training activities in technological environments. Distance education has also brought some difficulties as well as provided certain advantages to teachers. Quantitative analysis was preferred as the research method to describe the difficulties teachers faced when implementing open and distance education in Turkey. Within the scope of this study, problems of distance education faced by educators in classroom management are tried to be examined during the pandemic period.